T-Cell Lymphoblastic Leukemia/Lymphoma: Relapse 16 Years after First Remission. (13th April 2014) - Elreda, Lauren; Sandhu, Manpreet; Sun, Xinlai; Bekele, Wondwessen; Cohen, Alice J.; Shah, Maya
Abstract : Little information is available regarding late relapse in patients with T-lymphoblastic leukemia/lymphoma (T-LBL). Because of the aggressive nature of this disease, relapse is common and often happens early. Late relapses are rare and generally occur within a few years after initial remission. The relapse rate after 3 years has been reported to steadily decrease over time yet does not parallel with cure. We report a case of a 26-year-old female with T-LBL and relapse 16 years after her first remission with successful treatment with HyperCVAD and L-asparaginase.